Are happiness and productivity lower among university students with newly-divorced parents? An experimental approach - Eugenio Proto; Daniel Sgroi; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2010)
We live in a high-divorce age. It is now common for university faculty to have students who are touched by a recent divorce. It is likely that parents themselves worry about effects on their children. Yet there has been almost no formal research into the important issue of how recent parental-divorce affects students at university. This paper designs such a study. In it, to avoid 'priming', we measure students' happiness with life before we inquire into their family background. We also measure student achievement in a randomized-trial productivity task. Our results seem both of scientific interest and of potential interest to parents. This study finds no evidence that students suffer after parental divorce.
Keywords: D03; J24; C91; 330; Labor productivity; divorce; well-being; happiness; experimental economics; Studierende; Lebenszufriedenheit; Arbeitsproduktivität; Familiensoziologie; Scheidung; Test; Großbritannien